Systematic observation: Helping you coach more effectively - Pearce, A. J.; Embrey, L. (Sports Coach, 2002)
Have your athletes reached a plateau? Despite everything you do and say, the improvements are minuscule? Perhaps then, it might be time to not only look at the athletes but also yourself. During every training session you constantly monitor your athletes' training behaviour, their fitness, skills and tactical abilities and give them feedback to improve themselves. But do you monitor yourself as closely? And if not, why not? By helping your own coaching behaviour you're ultimately helping your athletes. This article aims to give you some ideas to get you thinking about improving your own behaviour. The methods are time tested and have assisted coaches in numerous sports (Table I) around the world to im~roveth eir coachina.